Clinical Utility of Hemoglobin Testing After Minimally Invasive Sacrocolpopexy. Issue 1 (January 2018) - Lavelle, Erin Seifert; Giugale, Lauren; Sears, Sarah; Carter-Brooks, Charelle M.; Shepherd, Jonathan P.
Abstract : Objective: To determine the clinical utility of routine postoperative hemoglobin screening after minimally invasive sacrocolpopexy. Methods: This is a retrospective chart review of women undergoing minimally invasive sacrocolpopexy between 2009 and 2015 at a large academic center where postoperative hemoglobin assessment is performed as routine practice. Demographic and perioperative data, pre- and postoperative hemoglobin values, and clinical signs and symptoms of potential postoperative anemia were extracted. Hemoglobin parameters were compared between women with and without clinical evidence of potential postoperative anemia. Linear and logistic regression analyses were used to identify predictors of postoperative anemia and magnitude of hemoglobin decrease. Results: Among 800 women, postoperative hemoglobin was obtained for 99.6% and prompted further testing among 23.8%. Mean postoperative hemoglobin was 11.78 ± 1.11 g/dL, and mean decrease was 1.76 ± 0.95 g/dL. More than half (56.9%) had clinical evidence of potential anemia, but few (5%) had postoperative hemoglobin of 10 g/dL or less and none required transfusion. Women with clinical evidence of potential anemia had lower postoperative hemoglobin (11.57 vs 12.19; P < 0.001) and larger mean hemoglobin decrease (1.91 vs 1.49; P < 0.001). On regression analyses, only lower body mass index was associated with larger hemoglobin decrease ( β = −0.030, P < 0.001) and no factor significantly predicted postoperative hemoglobin of 10 g/dL or less. Conclusions: Routine hemoglobin testing rarely benefited clinical care but lead to further testing for nearly 1 in 4 patients. Although many women demonstrated clinical evidence potentially suggestive of anemia, significant anemia was rare and no women required transfusion. Neither estimated blood loss nor other risk factors consistently predicted presence of postoperative anemia or significant postoperative decrease in hemoglobin. Abstract : Routine hemoglobin testing rarely benefitted clinical care but led to further testing for nearly 1 in 4 patients.